The Effect of a Concentrated Mass on the Acoustic Power and the Resonant Frequencies of a Circular Plate - RDZANEK, Wojciech P.; SZEMELA, Krzysztof (Archives of Acoustics, 2022)
This study presents an analysis of the effect of the concentrated mass on the acoustic power and the resonant frequencies of a vibrating thin circular plate. The fluid-structure interactions and the acoustic wave radiation effect have been included. The eigenfunction expansion has been used to express the transverse displacement of the plate. The appropriate number of modes is determined approximately to achieve physically correct results. Then highly accurate results are obtained numerically. The radiated acoustic power has been used to determine the resonant frequencies. The introducing of the concentrated mass is justified by modelling the added mass of the moving component of the exciter.